Magnetospheric Interactions of Saturn's Moon Dione (2005–2015). Issue 6 (19th June 2020) - Krupp, N.; Kotova, A.; Roussos, E.; Simon, S.; Liuzzo, L.; Paranicas, C.; Khurana, K.; Jones, G. H.
Abstract: The moon Dione orbits Saturn at 6.2 Saturn radii R S deep in the Kronian magnetosphere. In situ studies of the moon‐magnetosphere interaction processes near Dione were possible with the Cassini/Huygens mission which flew by close to Dione five times at distances between 99 and 516 km. In addition, Cassini crossed Dione's L‐shell more than 400 times between 2004 and 2017 and documented the variability of Saturn's magnetosphere. Different flyby geometries allowed to study the interaction processes upstream, in the low‐energy wake, and above the north pole of Dione. We describe here the energetic particle measurements from the Low Energy Magnetospheric Measurement System (LEMMS), part of the Magnetosphere Imaging Instrument (MIMI) onboard Cassini. We also use hybrid simulation results from "A.I.K.E.F." to interpret the signatures in the particle fluxes. This paper is a continuation of Krupp et al. (2013, https://doi.org/10.1016/j.icarus.2013.06.007 ) and Kotova et al. (2015, https://doi.org/10.1016/j.icarus.2015.06.031 ). The key results are as follows: (1) Saturn's magnetosphere at Dione's orbit is highly variable with changes in energetic charged particle fluxes by 1–2 orders of magnitude. (2) The dropout signatures near Dione are basically consistent with a fully absorbing obstacle, but some features point to more complex interaction processes than plasma and energetic particle absorption. (3) Absorption signatures are found to be asymmetric with respect to the orientation of the moon, indicative of the presence of radial drift components for electrons. (4) The deepest absorption signatures were observed at the edge of the low‐energy wake pointing to gradient‐B drifts strongest in that part of the interaction region. Key Points: Dropout signatures in energetic particle fluxes near Dione are basically consistent with a fully absorbing obstacle Absorption signatures are found to be asymmetric with respect to the orientation of the moon, pointing to radial drift of electrons The deepest absorption signatures were observed at the edge of the low‐energy wake pointing to gradient‐B drifts